2020
DOI: 10.1037/vio0000264
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence and nonviolent life stressors and their relations to trauma-related distress and problem behaviors among urban early adolescents.

Abstract: Objective: The impact of exposure to violence must be considered within the context of a larger constellation of nonviolent life stressors faced by youth in underresourced communities. This study examined nonviolent life stressors, two types of violence exposure, and their associations with trauma-related distress and problem behaviors. Method: Participants were a predominantly African American (80%) sample of early adolescents (Mage = 12.9 years) living in communities with high rates of crime. Structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Perhaps adolescent's exposure to events over which they have little control (e.g., family members' behavior) reinforces perceptions that others are a threat, which reinforces reactively aggressive beliefs. This notion is in line with prior work that found that negative life events were more strongly related to post-traumatic stress symptoms (e.g., hyperarousal) than either witnessing or being the victim of community violence (Thompson et al, 2020). These findings also underscore the importance of accounting for concurrent negative life events when investigating the extent to which exposure to violence impacts youths' beliefs and behavior.…”
Section: Associations Between Exposure To Violence and Beliefssupporting
confidence: 88%
See 2 more Smart Citations
“…Perhaps adolescent's exposure to events over which they have little control (e.g., family members' behavior) reinforces perceptions that others are a threat, which reinforces reactively aggressive beliefs. This notion is in line with prior work that found that negative life events were more strongly related to post-traumatic stress symptoms (e.g., hyperarousal) than either witnessing or being the victim of community violence (Thompson et al, 2020). These findings also underscore the importance of accounting for concurrent negative life events when investigating the extent to which exposure to violence impacts youths' beliefs and behavior.…”
Section: Associations Between Exposure To Violence and Beliefssupporting
confidence: 88%
“…Participants rated their frequency of experiencing 20 stressful life events in the past 3 months on a 5point scale ranging from Never to Almost every day. Support for the construct validity of the UANLES was found in a cross-sectional study that sampled data from the same project used in the current study (Thompson et al, 2020), which found strong associations between the UANLES and latent variables representing trauma-related distress, physical aggression, delinquency, and substance use. The total score based on the average across items had an alpha of .81.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…No items involved witnessing or experiencing violence. The construct validity of the UANLES is supported by associations with trauma-related distress, physical aggression, delinquency, and substance use (Thompson et al, 2020). The total score was the mean rating across items.…”
Section: Methodsmentioning
confidence: 99%
“…Scores of studies have supported its construct validity based on correlations with other measures (see meta-analysis by Fowler et al, 2009). The project used a shortened version (Thompson, Coleman, et al, 2020) that had 13 witnessing violence items (e.g., “Seen someone else getting beaten up or mugged”) and seven victimization items (e.g., “Been attacked or stabbed with a knife”). Participants rated their frequency of witnessing or experiencing each item in the past 3 months on a 6-point scale ranging from Never to 20 or more times .…”
Section: Methodsmentioning
confidence: 99%